Donor–acceptor materials exhibiting deep blue emission and thermally activated delayed fluorescence with tris(triazolo)triazine. Issue 40 (5th October 2021) - Hojo, Ryoga; Mayder, Don M.; Hudson, Zachary M.
Abstract : Five emitters with the tris(triazolo)triazine acceptor core are reported, with emission from deep blue to green. These emitters show promising thermally activated delayed fluorescence and/or two-photon fluorescence properties. Abstract : Five luminescent donor–acceptor compounds based on the tris(triazolo)triazine (TTT) acceptor were prepared. Out of the series of emitters, TTT-3HMAT exhibits deep blue emission with CIE( x, y ) < (0.16, 0.05) and a photoluminescence quantum yield (PLQY) of 0.94 in toluene. In addition, the locked-planarity of the hexamethylazatriangulene (HMAT ) donors induced the highest two-photon cross-section σ 2 of 2928 GM, while the material also exhibited 2.9-fold enhancement in photostability compared to non-planarized triarylamines. In contrast, TTT-3TTAC undergoes thermally activated delayed fluorescence (TADF), attributed to the strongly donating and highly twisted nature of the N 3, N 3, N 6, N 6-tetra- p -tolyl-9 H -carbazole-3, 6-diamine(TTAC ) donor. Overall, this work uncovers the potential for TTT-based dyes for two-photon imaging while further revealing the structure–property relationships needed to design TTT-based emitters as TADF materials.